Effects of the COVID-19 pandemic on hip fracture volume, disposition, and readmission rates. Issue 4 (9th June 2022) - Helal, Asad; Botros, David; Qureshi, Fahad; Alhreish, Khalid; Dutcher, Lincoln; Teel, Jordan; Dawkins, Jonathon; Rizkalla, James
Abstract: Our study aimed to assess the effects COVID had on the incidence of hip fractures. Hip fracture cases (from March 1 to September 1) were compared in 2018, 2019, and 2020. Data were analyzed for surgical volume, discharge location, and readmission rates. There was a statistically significant decrease in hip fractures during 2020 ( P  < 0.01) and a decrease in patients placed in skilled nursing facilities ( P  = 0.04), with no increase in 30-day readmission ( P  = 0.776). Findings suggest that COVID-19 has impacted the volume and composition of hip fracture cases. Although additional research on the subsequent survival impact is necessary, these placement patterns of hip fracture patients into facilities may be an opportunity to optimize cost and care.